PENGARUH LEVERAGE, FREE CASH FLOW, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2013-2016) - Reina Widianingrum, 14.05.52.0159; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2018)
This study examines the effect of leverage, free cash flow, profitablility and size of the earning management on the manufacture companies listed on the Indonesia Stock Exchange. This study used purposive sampling method in sample selection, the criteria for a sample of the real estate and property companies listed in Indonesia Stock Exchange (IDX) during the period 2013-2016. Based on these criteria, obtained a sample of 84 companies over a four-year observation period. Or influence between variables described using multiple regression analysis method.The results showed that the variable leverage and size have no effect on the variable earnings management. Variable free cash flow have negative effect on the earnings management. Variabel profitability have positive effect on the earnings management. Keywords: Earnings Management, Leverage, Free Cash Flow, Profitability, Size.